ON FREE IDEALS IN FREE ALGEBRAS OVER A COMMUTATIVE RING - Wardati, Khurul; Wijayanti, Indah Emilia; Wahyuni, Sri (Journal of the Indonesian Mathematical Society, 2015)
Let A be a free R-algebra where R is a unital commutative ring. An ideal I in A is called a free ideal if it is a free R-submodule with the basis contained in the basis of A. The denition of free ideal and basic ideal in the free R-algebra are equivalent. The free ideal notion plays an important role in the proof of some special properties of a basic ideal that can characterize the free R-algebra. For example, a free R-algebra A is basically semisimple if and only if it is a direct sum of minimal basic ideals in A: In this work, we study the properties of basically semisimple free R-algebras.DOI :Â http://dx.doi.org/10.22342/jims.21.1.170.59-69